The WTO deadlocked : understanding the dynamics of international trade - Chakraborty, Debashis; Khan, Amir Ullah (New Delhi ; Thousand Oaks, Calif. : SAGE Publications, 2008)
"This book analyses the contemporary state of affairs at the World Trade Organization (WTO) and India's negotiating agenda at its various forums. The book identifies areas in the WTO agreements that require systematic reforms. It also discusses the negotiating history of GATT/WTO, especially after the conclusion of the WTO negotiations in 1995, while not overlooking the failures of the Seattle Ministerial and Doha negotiations. It delves into the rights and concerns of different interest-groups within the WTO."--BOOK JACKET.
Foreword / Biswajit Dhar -- 1. India and the WTO: The Increasing Participation at the Multilateral Level -- 2. Agreement on Agriculture: The Pandora's Box? -- 3. The SPS-TBT Measures and Environmental Concerns -- 4. NAMA Negotiations: The Way Ahead -- 5. Trade in Textiles and Clothing in the Post-MFA Period -- 6. Anti-Dumping, Subsidy, and Countervailing Measures and Safeguards Mechanism: The Battle Over Contingency Measures -- 7. Intellectual Property Rights: Where Do We Stand? -- 8. Trade in Services: Emerging Key Interest Area -- 9. Regionalism in the Era of Multilateralism: The Changing Focus -- 10. Ensuring an Efficient Dispute Settlement System at the WTO -- 11. Looking beyond Hong Kong: What Next for India?
Includes bibliographical references (p. [298]-320) and index.
Newaz
Keywords: World Trade Organization; International trade -- India; India -- Commercial policy